The Sexual Development, Sexual Health, Sexual Experiences, and Sexual Knowledge of Forensic Mental Health Patients: A Research Design and Methodology Protocol - Brand, Elnike; Ratsch, Angela; Heffernan, Edward (Frontiers in psychiatry, 2021)
Introduction: There is substantial evidence that severe mental illness (SMI) can have significant impacts on general development, knowledge acquisition, and quality of life including sexual function. However, whilst the sexual development, sexual health, sexual experiences and sexual knowledge of the broader Australian community and the Australian prisoner population have been well-described, these concepts have been less explored in people with a SMI. In particular, there is an absence of research around these topics involving people who are subject to a treatment order (aka a Forensic Order) under the relevant jurisdictional Mental Health Act. Methods and Analysis: People currently under the treatment requirements of a Queensland Forensic Order will be invited to participate in this descriptive, mixed-method study. The study will be conducted in three phases. The first two phases will involve 50 participants (100 face-to-face quantitative interviews) with the aim of mapping sexual development, sexual health, sexual experiences, and sexual knowledge. The third phase will involve qualitative semi-structured interviews with a purposely enrolled, informant-rich cohort identified through the quantitative surveys until saturation is reached. Quantitative data will be analyzed using descriptive and comparative statistics. Qualitative data will be analyzed by content analysis of the major themes. Ethics and dissemination: The project has ethics approval from a Queensland Health Human Research Ethics Committee. Results will be reported to participants and other stakeholders at seminars and conferences and through peer-reviewed publications. Strengths and Limitations of this Study: This is a mixed-method study which engages with participants by using face-to-face interviews. The study is conducted in three phases which sub-divide the research into the following areas: (1) demographics, general health, and sexual health, (2) sexual knowledge and experiences, and (3) sexual knowledge gaps. This study uses electronic data capture to efficiently record and analyse participant responses. This study captures self-reported data and uses non-probability sampling from a population who have been pre-selected through an arms-length approach—both these processes elevate the risk of bias.